2015
DOI: 10.1097/aln.0000000000000639
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Decreases Fluid Requirements and Blood Loss While Preserving Intestinal Villi Microcirculation during Fluid Resuscitation of Uncontrolled Hemorrhagic Shock in Mice

Abstract: During MAP-directed resuscitation of uncontrolled hemorrhagic shock, the administration of norepinephrine decreased blood loss and fluid requirements while preserving intestinal villi microcirculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
3
23
0
4
Order By: Relevance
“…disproved the above argument. [27] In this study, 42 mice were subjected to uncontrolled hemorrhage and were then randomly allocated into various groups treated with no fluids, fluids alone, or fluids and norepinephrine infusion. The MAP was maintained between 50 and 60 mmHg, and the intestinal microcirculation was observed by intravital microscopy.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…disproved the above argument. [27] In this study, 42 mice were subjected to uncontrolled hemorrhage and were then randomly allocated into various groups treated with no fluids, fluids alone, or fluids and norepinephrine infusion. The MAP was maintained between 50 and 60 mmHg, and the intestinal microcirculation was observed by intravital microscopy.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The vascular effects of recruiting a and b adrenoreceptors may prove to be beneficial in conditions of shock where excessive volume resuscitation may eventually lead to volume overload and increased morbidity. 76,77 Recent studies on mice demonstrated improved recovery from hemorrhagic shock when norepinephrine infusion was included in the treatment regimen 78 as it decreased the amount of fluid needed to maintain adequate hemodynamics. Moreover, that study demonstrated that the intestinal villi microcirculation was much better preserved when norepinephrine was included in the treatment.…”
Section: Effects Of Vasoactive Drugs Used During Gdhtmentioning
confidence: 99%
“…[86][87][88] Because such patients have significant impairment in vascular tone, their Vu remains large and Vs inadequate and the infused fluid ends up more in the Vu than Vs, and CO does not increase. Some data 56,64,[77][78][79][80] we presented and analyzed in the section on vasoactive drugs may justify the hypotheses that fluid therapy combined with small doses of venoconstricting drugs achieves a more beneficial distribution of infused fluid between the Vu and Vs and prevents fluid overload in the perioperative setting.…”
Section: Effects Of Vasoactive Drugs Used During Gdhtmentioning
confidence: 99%
“…Uncontrolled hemorrhage shock model in mice compared fluid requirements, blood loss, and intestinal microcirculation between fluid (i.e., 0.9 % saline) resuscitation with or without norepinephrine to target MAP at 50 and 60 mmHg [ 60 ]. The administration of norepinephrine significantly decreased fluid requirements by 60 % for MAP at 50 mmHg and 70 % for MAP at 60 mmHg compared to resuscitation only with fluid.…”
Section: Reviewmentioning
confidence: 99%